Options for a New Canada - Watts, Ronald L.; Brown, Douglas M. (Douglas Mitchell), 1954- (Book collections on Project MUSE., 1991)
Recognizing that Canada is facing a renewed and potentially disastrous constitutional impasse, the Business Council on National Issues has commissioned the papers in this book to provide a fresh analysis of our difficult constitutional problems.